A Model of Transiting Individual Efforts to the Outcomes of Virtual Team - Liu, Y.; Lin, Chad; Li, F. (Sungkyunkwan University, Suwon, Korea, 2010)
Few studies have formulated how individuals contribute to the team process and bring the success of virtual teams. The researcher attempted to integrate Technology-Task fit (TTF), Self-disclosure and Social Networks to build a framework to formulate how individual efforts are transited to the outcome of virtual teams. This framework was validated by an experiment which was engaged in a Wiki system. The results revealed that virtual team members interact by computer-mediated communication (CMC), the social relations were formed and gradually the team was tied together as a group. The efforts of each member are integrated by social ties in order to accomplish the goals. Three suggestions were proposed: (a) an appropriate technology which fits to the tasks should be provided; (b) an adequate training of operating the technology and disclose is needed to help members convey social cues and information to accomplish the tasks; (c) a mechanism to ensure the social ties go on the right track is crucial such as the frequency of communication and the way of solving conflicts.